Ventilation, thermal and luminous autonomy metrics for an integrated design process. (November 2018) - Ko, Won Hee; Schiavon, Stefano; Brager, Gail; Levitt, Brendon
Abstract: This paper proposes and evaluates an integrated workflow that simultaneously uses ventilation, thermal, and luminous autonomy for the assessment of passive design strategies, introducing a potential way to integrate these three metrics in the design process. We developed a new metric, ventilation autonomy, and assessed the advantages and limitations of applying the three autonomy metrics with building performance simulations in two climates. We developed a novel visualization to display the hourly and yearly environmental autonomy values. The results show that when we consider the three metrics together, designers may have contradicting design directions if trying to both mitigate the solar radiation and to utilize natural ventilation. The visualizations that categorize nine combinations of thermal and visual comfort along with ventilation autonomy are effective in showing the trade-offs among ventilation, thermal, and visual performance. Graphical abstract: Highlights: We develop, define and assess a new metric, ventilation autonomy. We propose an integrated workflow for luminous, thermal, and ventilation autonomy. We evaluate the advantages and limitations with building performance simulations. Major trade-offs between mitigating solar radiation and using natural ventilation.